Evidence Based Nursing Self-Management untuk Mengurangi Konstipasi pada Pasien Kanker Payudara yang Menjalani Kemoterapi: A Literature Review - Annisa Nur laili; Rofianto Adi Prasetyo; Herna Slamet Nuryana; Uti Uswatun Nisa; Nur Istiqomah (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Introduction: Breast cancer is a protrusion or abnormal growth in the breast area, cancer patients are usually treated with chemotherapy. In the administration of chemotherapy, especially the frequency of administration can cause several effects such as nausea, vomiting, constipation, weight loss, loss, diarrhea, changes in taste, and changes in emotions. Method: Search journal articles electronically through several databases including Google Scholar, Science Direct, Proquest, and Pubmed. Search is done using English that is relevant to the topic. The keywords used are